Encapsulation of yeast (Saccharomyces cereviciae) by spray drying for extension of shelf life - Chandralekha, A.; Tavanandi, A. Hrishikesh; Amrutha, N.; Hebbar, H. Umesh; Raghavarao, K. S. M. S.; Gadre, Ramchandra V. (Drying Technology, 2016)
The objective of the present work was to encapsulate yeast using different carrier materials and examine their efficacy in retaining viability of cells after spray drying. Slurry containing yeast cells along with known amount of carrier material (maltodextrin, corn starch, gum arabic, acacia gum, polyethylene glycol 8000, -cyclodextrin, and skimmed milk powder, one at a time) was added and served as feed. Among these carrier materials attempted, corn starch and maltodextrin showed the best results with respect to powder yield (59%, w/w) and cell survival (80.5%), respectively. However, considering both survival and powder yield (67 and 59% w/w, respectively), corn starch was observed to be the most suitable carrier material.
Keywords: Cell viability; Encapsulation; freeze-drying; spray drying; Yeast